Coordinative Study of Organic Material on Silver Nanoparticles and Its Application for Colorimetric Sensor - Rahayu, Setiya; Hidayah, Yoda Taruna; Syakuro, Qoid Abrori; Ronald, Azza Azahra; Herman; Wulandari, Priastuti (Spektra: Jurnal Fisika dan Aplikasinya, 2025)
Metal nanoparticles, especially gold and silver nanoparticles, have been applied in various fields of nanotechnology because of their unique optical properties called localized surface plasmon resonance (LSPR). Metal nanoparticles need capping material to stabilize and protect the metal core. The interaction between capping and metal core affects the physical and chemical properties of metal nanoparticles. Silver nanoparticles have a robust extinction coefficient compared to other metals of the same size. In addition, silver nanoparticles have been found to have antimicrobial properties. There has been a lot of research on the coordination between organic molecules with silver metal. However, the study about the coordination between organic molecules on silver nanoparticles has not been studied in detail. For this reason, the synthesis of silver nanoparticles capped by citrate (AgCA) and silver nanoparticles capped by 3-MPA (AgMPA) was optimized in order to form stable colloids. The interaction between capping molecules (citrate and 3-MPA) and silver core was studied experimentally and computationally. In the results, some different vibration peak positions of chemical coordination between free carboxylate and the carboxylate on silver nanoparticles were found, indicating the effect of strong chemical bonding and the effect of localized surface plasmon. Agreement was found between the experimental results and the calculation based on DFT simulation, which shows the same tendencies of vibration peak position. Moreover, colorimetric testing with Biocytin-Avidin was performed as a sensor application in the experiment.